An Enriched Environment Alters DNA Repair and Inflammatory Responses After Radiation Exposure - Sakama, Sae; Kurusu, Keisuke; Morita, Mayu; Oizumi, Takashi; Masugata, Shinya; Oka, Shohei; Yokomizo, Shinya; Nishimura, Mayumi; Morioka, Takamitsu; Kakinuma, Shizuko; Shimada, Yoshiya; Nakamura, Asako J. (Frontiers in Immunology, 2021)
After the Fukushima Daiichi Nuclear Power Plant accident, there is growing concern about radiation-induced carcinogenesis. In addition, living in a long-term shelter or temporary housing due to disasters might cause unpleasant stress, which adversely affects physical and mental health. It’s been experimentally demonstrated that “eustress”, which is rich and comfortable, has beneficial effects for health using mouse models. In a previous study, mice raised in the enriched environment (EE) has shown effects such as suppression of tumor growth and enhancement of drug sensitivity during cancer treatment. However, it’s not yet been evaluated whether EE affects radiation-induced carcinogenesis. Therefore, to evaluate whether EE suppresses a radiation-induced carcinogenesis after radiation exposure, in this study, we assessed the serum leptin levels, radiation-induced DNA damage response and inflammatory response using the mouse model. In brief, serum and tissues were collected and analyzed over time in irradiated mice after manipulating the raising environment during the juvenile or adult stage. To assess the radiation-induced DNA damage response, we performed immunostaining for phosphorylated H2AX which is a marker of DNA double-strand break. Focusing on the polarization of macrophages in the inflammatory reaction that has an important role in carcinogenesis, we performed analysis using tissue immunofluorescence staining and RT-qPCR. Our data confirmed that EE breeding before radiation exposure improved the responsiveness to radiation-induced DNA damage and basal immunity, further suppressing the chronic inflammatory response, and that might lead to a reduction of the risk of radiation-induced carcinogenesis.